Beta‐tricalcium phosphate ceramic triggers fast and robust bone formation by human mesenchymal stem cells. (15th April 2019) - Pereira, Rui C.; Benelli, Roberto; Canciani, Barbara; Scaranari, Monica; Daculsi, Guy; Cancedda, Ranieri; Gentili, Chiara
Abstract: Due to their osteoconductive and inductive properties, a variety of calcium phosphate (CaP) scaffolds are commonly used in orthopaedics as graft material to heal bone defects. In this study, we have used two CaP scaffolds with different hydroxyapatite (HA) and β‐tricalcium phosphate (β‐TCP) ratios (MBCP®; 60/40 and MBCP + ®; 20/80) to investigate their intrinsic capacity to favour human bone marrow stem cells (hBMSCs) osteogenic differentiation capacity. We report that MBCP + ® showed in in vitro culture model a higher rate of calcium ion release in comparison with MBCP®. In two defined coculture systems, the hBMSC seeded onto MBCP + ® presented an increased amount of VEGF secretion, resulting in an enhanced endothelial cell proliferation and capillary formation compared with hBMSC seeded onto MBCP®. When both ceramics combined with hBMSC were implanted in a nude mouse model, we observed a faster osteogenic differentiation and enhancement mature bone deposition sustained by the presence of a vast host vasculature within the MBCP + ® ceramics. Bone formation was observed in samples highly positive to the activation of calcium sensing receptor protein (CaSr) on the surface of seeded hBMSC that also shown higher BMP‐2 protein expression. With these data we provide valuable insights in the possible mechanisms of ossification and angiogenesis by hBMSC that we believe to be primed by calcium ions released from CaP scaffolds. Evidences could lead to an optimization of ceramic scaffolds to prime bone repair.